114 VATS ESOPHAGECTOMY: DOES PATIENT OPERATIVE POSITION DURING THORACOSCOPIC MOBILISATION INFLUENCE OUTCOMES? A PROSPECTIVE COMPARATIVE STUDY. (14th September 2020) - Choudhary, Y; Pokharkar, H; Patil, A; Mistry, R
Abstract: : VATS esophagectomy can be done in lateral, prone and semiprone positions. Present evidence available comparing semiprone with lateral position is retrospective. We have conducted this study to provide prospective data on perioperative outcomes in patients undergoing Video Assissted Thoracoscopic (VATS) esophagectomy in Semiprone (SP) and Lateral decubitus position (LP) in a single centre. Methods: 48 patients (SP =24 & LP =24) undergoing VATS esophagectomy (2017 to 2019) were analysed. Preoperative details (tumor characteristics, preoperative treatment and pulmonary function test), intraoperative details [operative time, blood loss, mean EtCO2, arterial blood gas analysis (ABG) at the end of one lung ventilation(OLV), number of ports used, need for lung reinflation and retraction] and postoperative details [duration of ICU stay, cardiovascular and respiratory complications, pain scores (VAS) and tidal volume improvement (spirometry reading) on first five postoperative days, circumferential resection margin (CRM) status, total and recurrent laryngeal nerve (RLN) nodal yield were noted. Results: Preoperative data in both arms were comparable. Ports used (5 vs 3, p < 0.0001), need for lung retraction (22 vs 4patients, p < 0.0001), duration of ICU stay (2 days vs 1 day, p = 0.0327), spirometry readings for POD 1st-5th (p < 0.05) and pain scores (p < 0.05) for POD 1st-5th was significantly less in SP group. There were fewer respiratory complications in SP group (10 vs 4, p = 0.110). LP group had shorter duration of surgery (3.7 vs 4.2 hours, p = 0.0398). There were no differences in tumor characteristics, blood loss, ABG at the end of OLV, mean EtCO2, lung reinflation rate, cardiovascular complications, CRM involvement, total and RLN nodal yield. Conclusion: Similar oncological clearance was achieved by both techniques of esophageal mobilization. Semiprone position is associated with lesser postoperative pain and better preservation of respiratory function.